Safety Induction Socialization at The Pakupatan Untirta Campus to Create a Safe Campus - Mariawati, Ade Sri; Herlina, Lely; Dewantari, Nustin Merdiana (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Security and safety on campus are significant aspects of creating a conducive environment for the learning process. Pakupatan Untirta Campus, as a place inhabited by students, lecturers, and staff, has potential risks that can threaten safety. Therefore, socialization regarding safety induction is needed to equip the academic community with knowledge regarding preventive measures, evacuation procedures, use of safety equipment, and emergency steps that must be taken in various risky situations. This study aims to provide comprehensive knowledge to the academic community regarding safety and to create a safe campus. The methods used in this study include four steps: identifying safety risks, determining gathering points, creating evacuation routes, and creating safety induction videos as a means of socialization. The results showed that of the 11 buildings on the Pakupatan Campus, only six were equipped with light fire extinguishers (APAR). The designated gathering point is on the sports field, an area of 1,215 m². The layout for the evacuation route has also been clearly described. In addition, a safety induction video was crafted to support the socialization of safety on campus. In conclusion, this community service program was successfully implemented and presents a significant contribution to increasing understanding and awareness of safety on the Pakupatan Untirta Campus.